Ծանրակշիռ գիտական ուսումնասիրութիւն թումանեանագիտութեան բնագաւառում - Մարգարեան, Սիրանոյշ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В конце 2024 года по решению ученого совета Института литературы имени Манука Абегяна НАН РА вышло в свет масштабное исследование доктора филологических наук Евы Мнацаканян «Произведения Ованеса Туманяна в оценке литературно-критической мысли своего времени». За последние 130 лет критическая мысль проявила исключительный интерес к личности всеармянского поэта, его творческим поискам, отдельным произведениям, а также к его национально-общественной и культурной деятельности. Автор исследования предпринял целостное исследование публикуемых в течение более трех десятилетий критических отзывов на творчество Туманяна. Собранный разнородный и объемный материал: газетные передовицы, статьи, рецензии, крупные и небольшие монографические исследования Мнацаканян подвергла научному и системному анализу. Статья посвящена рассмотрению проблем, выдвинутых в исследовании Евы Мнацаканян, а также связанных с Туманяном и его литературной эпохой многочисленных вопросов, оставшихся нерешенными и заслуживающих изучения. At the end of 2024, following a decision by the Academic Council of the Institute of Literature after M. Abeghyan of the National Academy of Sciences of Armenia, a large-scale study by Eva Mnatsakanyan, Doctor of Philology, entitled “The Works of Hovhannes Tumanyan in the Assessment of Literary and Critical Thought of His Time” was published. Over the past 130 years, the critical thought has shown exceptional interest in the personality of the pan-Armenian poet, his creative pursuits, individual works, as well as his national, social, and cultural activities. The author of the study undertook a comprehensive study of critical reviews of Tumanyan’s works published over more than three decades. Mnatsakanyan conducted a scientific and systematic analysis of the diverse and voluminous material she had collected, namely: newspaper editorials, articles, reviews, and large and small monographic studies. The article is devoted to the consideration of the problems raised in Yeva Mnatsakanyan’s study, as well as numerous issues related to Tumanyan and his literary era that remain unresolved and deserve study.
Keywords: Գրախօսութիւն